Prevalence of abdominal obesity and its association with cardiovascular risk among the adult population in Burkina Faso: findings from a nationwide cross-sectional study. Issue 7 (6th July 2021) - Cisse, Kadari; Samadoulougou, Sékou; Ouedraogo, Mady; Kouanda, Seni; Kirakoya-Samadoulougou, Fati
Abstract : Objective: The objective of this study is to determine the prevalence of abdominal obesity, its predictors and its association with cardiovascular risk among adults in Burkina Faso. Design: We performed a secondary analysis of data from a national cross-sectional study, using WHO STEPwise approach. Setting: The study was conducted in Burkina Faso, in all the 13 regions of the country. Participants: Our study involved 4308 adults of both sexes, aged between 25 and 64 years. Primary and secondary outcomes: Our primary outcome was abdominal obesity, which was defined using a cut-off point of waist circumference (WC) of ≥94 cm for men and ≥80 cm for women. The secondary outcome was very high WC (≥102 cm for men and ≥88 cm for women) (for whom weight management is required). Results: The mean age of participants was 38.5±11.1 years. The age-standardised prevalence of abdominal obesity was 22.5% (95% CI 21.3% to 23.7%). This prevalence was 35.9% (95% CI 33.9% to 37.9%) among women and 5.2% (95% CI 4.3% to 6.2%) among men. In urban areas, the age-standardised prevalence of abdominal obesity was 42.8% (95% CI 39.9% to 45.7%) and 17.0% (95% CI 15.7% to 18.2%) in rural areas. The age-standardised prevalence of very high WC was 10.2% (95% CI 9.3% to 11.1%). The main predictors of abdominal obesity were being female, increased age, married status, high level of education and living in urban areas. Abdominal obesity was also significantly associated with high blood pressure (adjusted prevalence ratio (aPR): 1.30; 95% CI 1.14 to 1.47) and hypercholesterolaemia (aPR: 1.52; 95% CI 1.18 to 1.94). According to the combination matrix between body mass index and WC, 14.6% of the adult population in Burkina Faso had an increased cardiometabolic risk. Conclusion: Our study showed a high prevalence of abdominal obesity and a high proportion of adults who require weight management strategies to prevent cardiometabolic complications. Strategies to reduce the burden of abdominal obesity and very high WC should be considered by Burkina Faso's policy-makers.